2000
DOI: 10.1016/s0960-9822(00)00563-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and cognitive contributions of color to the recognition of natural scenes

Abstract: Although color plays a prominent part in our subjective experience of the visual world, the evolutionary advantage of color vision is still unclear [1] [2], with most current answers pointing towards specialized uses, for example to detect ripe fruit amongst foliage [3] [4] [5] [6]. We investigated whether color has a more general role in visual recognition by looking at the contribution of color to the encoding and retrieval processes involved in pattern recognition [7] [8] [9]. Recognition accuracy was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
213
3
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(238 citation statements)
references
References 19 publications
10
213
3
12
Order By: Relevance
“…these generally good outcomes stand in contrast with the delayed-cue procedural failures that have been reported with participants who functioned at very low behavioral levels (e.g., Oppenheimer, Saunders, & Spradlin, 1993). Perhaps our generally good findings were due in part to the combined use of the delayed S+ and delayed cue procedures in the context of a task that required discrimination of salient stimuli: food items or tokens that could be exchanged for food that differed along a primitive stimulus dimension, color (Gegenfurtner & rieger, 2000). regarding points of particular interest within the data set, we note that all participants displayed a large number of responses during tS1, specifically during delayed S+ training.…”
Section: Delayed Cue Trainingcontrasting
confidence: 61%
“…these generally good outcomes stand in contrast with the delayed-cue procedural failures that have been reported with participants who functioned at very low behavioral levels (e.g., Oppenheimer, Saunders, & Spradlin, 1993). Perhaps our generally good findings were due in part to the combined use of the delayed S+ and delayed cue procedures in the context of a task that required discrimination of salient stimuli: food items or tokens that could be exchanged for food that differed along a primitive stimulus dimension, color (Gegenfurtner & rieger, 2000). regarding points of particular interest within the data set, we note that all participants displayed a large number of responses during tS1, specifically during delayed S+ training.…”
Section: Delayed Cue Trainingcontrasting
confidence: 61%
“…On this basis, the authors argued for comparatively late effects of color in recognition. In contrast, Gegenfurtner (1998) showed that tachistoscopic (30-50 ms) presentations of colored pictures elicited better retrieval from memory than their luminance counterparts, illustrating that chromatic cues can index scene memory. This color advantage occurred irrespective of whether the target represented a human-made (e.g., streets) or a natural scene (e.g., flowers and landscapes).…”
Section: Luminance Color and Recognitionmentioning
confidence: 80%
“…For example, very brief presentations of natural scenes are matched more accurately by subjects when shown in color than when shown as luminance-controlled grey-scale images, which indicates that color provides an important source of information in the pre-recognition stage of visual processing (Gegenfurtner & Rieger, 2000). According to Gegenfurtner and Rieger (2000), color information contributes at both the sensory (coding) and cognitive (representation) levels of information processing for object recognition in natural scenes. More recently, Tanaka et al (2001) proposed an object recognition model, the "Shape + Surface" model of object recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies suggest that the function of color in object recognition is not well understood and there is no agreement concerning its role in object naming/recognition. Furthermore, there are some evidence suggesting that, at a lower visual processing level, color helps to diVerentiate objects (Gegenfurtner & Rieger, 2000;Wurm, Legge, Isenberg, & Luebker, 1993). For example, very brief presentations of natural scenes are matched more accurately by subjects when shown in color than when shown as luminance-controlled grey-scale images, which indicates that color provides an important source of information in the pre-recognition stage of visual processing (Gegenfurtner & Rieger, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation